Exploring the Barriers to Internationalisation for Malaysian SMEs - Hasim, Muhammad Asyraf; Ishak, Mohd Fikri; Shamsudin, Mohd Farid (International Journal of Engineering and Technology, 2018)
SMEs had posed a significant contribution toward Malaysian economy in term of GDP and a source of employment. However, in spite of internationalisation benefits that promote SMEs growth, Malaysian SMEs involvement in cross border activity is relatively low. Therefore, it is crucial for SMEs to mitigate such barriers that inhibit their cross-border activities in reaping the benefit offers by globalised marketplace. This study aims to determine the barriers to internationalisation faced by Malaysian SMEs. Qualitative method of research was employed, using asynchronous web-based semi-structured interviews. The interview questionnaires comprised eighteen questions and were designed and conducted using approved online interview guidelines. Twenty useable interviews were obtained and analysed using NVivo program in relation to qualitative content analysis technique. This study found that barriers to internationalisation faced by Malaysian SMEs were mainly due to firm’s internal deficiencies that inhibit internationalisation. The findings can be used in the development of policy aimed at supporting and encouraging internationalisation among SMEs in Malaysia. The findings also contribute to the existing body of knowledge in SMEs study.